The protective effect of alpha-lipoic acid against oxidative damage in rabbit conjunctiva and cornea exposed to ultraviolet radiation - Demir, Ü; Demir, T; Ilhan, N (Karger, 2005)
Purpose: The purpose of this study was to determine the protective effect of alpha-lipoic acid against oxidative damage in rabbit conjunctiva and cornea exposed to ultraviolet radiation. Methods: 20 rabbits weighing 2,500 3,000 g were used, and we divided them into 4 groups with 5 randomly selected rabbits. The rabbits were exposed to 2 J/cm(2)/h of ultraviolet A radiation (UVA) in the range of 320 - 405 nm for 12 h per day within 90 days. The control group did not undergo any procedure, the UVA group was only exposed to UVA radiation. The PUVA group was treated with 8-methoxypsoralen and UVA. The alpha-lipoic acid group was administered 8-methoxypsoralen + UVA + alpha-lipoic acid. At the end of 90 days, the rabbits were killed by decapitation, and the eyes were enucleated. Both eyes of each rabbit were used for biochemical evaluation. Conjunctival and corneal free malondialdehyde (MDA), glutathione peroxidase (GSH-PX) and superoxide dismutase ( SOD) levels were compared among the groups. Results: Conjunctival free MDA levels were lower in the alpha-lipoic acid group compared with the UVA and PUVA groups ( p < 0.05, p < 0.001, respectively). Both conjunctival SOD levels ( p < 0.05, p < 0.01, respectively) and conjunctival GSH-PX levels ( p < 0.01, p < 0.001, respectively) were higher in the alpha-lipoic acid group compared with other groups. Corneal free MDA levels were lower in the alpha-lipoic acid group compared with the UVA and PUVA groups ( p < 0.01, p < 0.001, respectively). Both corneal SOD levels ( p < 0.01, p < 0.01, respectively) and corneal GSH-PX levels ( p < 0.01, p < 0.01, respectively) were higher in the alpha-lipoic acid group compared with the other groups. Conclusion: alpha-Lipoic acid which is considered as potent antioxidant protects the eye from the damaging effect of ultraviolet exposure. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: alpha-lipoic acid; psoralen-UVA therapy; ultraviolet A radiation; antioxidants